A Transient Developmental Background Finding in the Retina Observed in Neonatal Dogs in Juvenile Toxicology Studies. (June 2019) - Petruska, Janet M.; Remick, Amera K.; Lejeune, Typhaine; Vezina, Mark; Robinson, Keith; Bussières, Martin; Gilger, Brian C.; Dubielzig, Richard R.
In a juvenile toxicology program, an unexpected finding of vacuolation of inner nuclear, ganglion cell, and nerve fiber layers of the retina was observed microscopically in routine Davidson's fixed and hematoxylin and eosin–stained tissue sections of eyes in beagle dogs at approximately 5 weeks of age. There was no necrosis or degeneration of the affected cells and no associated inflammation. Fluorescein angiography revealed no vascular leakage. Optical coherence tomography (OCT) indicated swollen cells in the same layers of the retina as observed at light microscopic examination. Transmission electron microscopy revealed that the retinal vacuolation likely was consistent with intracellular swelling of amacrine, horizontal, and/or bipolar cells of the inner nuclear layer as affected cells had an expanded cytoplasm but contained normal nucleus and organelles. As assessed by animal behavior and full-field electroretinography, the retinal vacuolation appeared to have no impact on visual function. Retinal vacuolation was seen in approximately 40% of dogs at 5 weeks of age using OCT and/or light microscopic examination. Because the change was transient and age related, did not result in degenerative retinal changes, and was not present in dogs older than 5 weeks of age, it was considered a background developmental observation in beagle dogs.